Preparing Malaysian youths for the world of work: roles of technical and vocational education and training (TVET) - Bakar, Ab. Rahim (Universiti Putra Malaysia Press, 2011)
Technical and vocational education and training (TVET) refers to those aspects of the educational process involving, in addition to general education, the study of technologies and related sciences, acquisition of practical skills and attitudes, and understanding and knowledge related to occupations in various sectors of economic and social life (UNESCO, 2002b). TVET plays a significant role in providing a highly skilled workforce for the development of many countries. TVET is an instrument of social policy. It assists people in certain social groups such as those in poverty or who lack marketable skills (Basu, 1997) to improve themselves. In fact, TVET can alleviate the socio-economic status of those in poverty. TVET produces human resources that have both soft skills and technical skills or the work skills required by the new economy. TVET is an indispensable instrument that helps improve the quality of the workforce by improving their mobility, adaptability and productivity (Caillods, 1994). Thus, TVET can contribute to the enhancement of the competitiveness of any organization in the globalized world. TVET is well placed to train skilled and entrepreneurial workforce required by some countries to create wealth and emerge from poverty because TVET orients itself towards the world of work with a curriculum that emphasizes on the acquisition of employable skills (Afeti, 2006). As TVET is very important in the development of a nation, it has to be promoted at both secondary school level and post-secondary school level. TVET should be emphasized in the national human-capital development policy because TVET is the key to both economic growth and to providing individuals economic opportunities. The perception of second-class status presently accorded to TVET should be removed by taking steps such as having an articulation agreement with post secondary institutions and giving due recognition to TVET qualifications